1980
DOI: 10.1029/gl007i005p00309
|View full text |Cite
|
Sign up to set email alerts
|

Rocket observations of precipitating electrons over a pulsating aurora

Abstract: Data from the third rocket of the Substorm‐GEOS series have been studied. The rocket was launched from ESRANGE on January 27, 1979 at 21.52.20 UT into a pulsating aurora. Measurements were performed in the energy range 0‐33 keV with electrostatic analyzers and above 48 keV with solid state detectors. The pulsations are visible in the data above 3‐4 keV. In a pulsation maximum the bulk of the energy flux is carried by electrons of energies between 5 and 40 keV. In pulsation minima the bulk of the energy flux is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

21
101
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(123 citation statements)
references
References 13 publications
(12 reference statements)
21
101
1
Order By: Relevance
“…Such enhancements lead to the attenuation of HF radio signals, often referred to as auroral absorption, which we measure as cosmic noise absorption (CNA). It has also been suggested that this occurs in association with pulsating aurora, which are known to have a hard precipitating energy spectrum (Stenbaek-Nielsen and Hallinan, 1979;Sandahl et al, 1980), and so are expected to produce enhancement of the D region electron density. One of our events is certainly associated with pulsating aurora.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such enhancements lead to the attenuation of HF radio signals, often referred to as auroral absorption, which we measure as cosmic noise absorption (CNA). It has also been suggested that this occurs in association with pulsating aurora, which are known to have a hard precipitating energy spectrum (Stenbaek-Nielsen and Hallinan, 1979;Sandahl et al, 1980), and so are expected to produce enhancement of the D region electron density. One of our events is certainly associated with pulsating aurora.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, such spectral widths are comparable to those of meteor echoes, in which the decorrelation of the radar auto correlation function is governed by the rate of ambipolar diffusion of the plasma trail rather than ionospheric instability growth and decay times (Hall et al, 1997;). The energy spectrum of precipitating electrons associated with pulsating aurora is expected to be relatively hard (Stenbaek-Nielsen and Hallinan, 1979), the bulk of the energy flux being carried by electrons between 5 and 40 keV (Sandahl et al, 1980) which produce excess ionization at altitudes below the E region peak. speculated that spatially-structured precipitation -and the resulting spatially-structured electron density enhancement -could allow backscatter from these low altitudes, and that the decay of the irregularities would be governed by the ambipolar diffusion rate.…”
Section: Introductionmentioning
confidence: 99%
“…Early rocket observations from Sandahl et al [1980] showed that the pulsations were visible in the data above 3 keV and that the bulk of the energy flux was carried by electrons with energies between 5 keV and 40 keV. They also reported detecting electron energies of up to 140 keV that were modulated with the pulsating aurora.…”
Section: Introductionmentioning
confidence: 99%
“…Bryant et al, 1975;Sandahl et al, 1980;McEwen et al, 1981;. Sandahl et al (1980) and McEwen et al (1981) found that the electron precipitation during pulsation minima had a lower mean energy than the precipitation during pulsation maxima. Quantifying the energy flux in auroral pulsations gives a measurement of the energy transfer from the magnetosphere to the ionosphere during these long-lasting and ubiquitous events.…”
Section: Introductionmentioning
confidence: 99%
“…Rocket and satellite measurements have shown that pulsating aurora is the result of modulated electron fluxes with energies from a few to several tens of kilo-electronvolts (e.g. Bryant et al, 1975;Sandahl et al, 1980;McEwen et al, 1981;. Sandahl et al (1980) and McEwen et al (1981) found that the electron precipitation during pulsation minima had a lower mean energy than the precipitation during pulsation maxima.…”
Section: Introductionmentioning
confidence: 99%